The Correlation of Self Efficacy To Physical Exercise Compliance in Type 2 Diabetes Mellitus Patients (HEALTH CARE: JURNAL KESEHATAN, 2024)
Less than optimal management of diabetes mellitus causes one of the high rates of DM, this is related to the patient's low self-efficacy. Can be seen in Indonesia that diabetes is ranked fifth among as many as 19.47 million. This study aims to determine the relationship of self-efficacy to physical exercise compliance in patients with type 2 diabetes mellitus. The type of research used is quantitative with a cross-sectional approach with a sample of 81 respondents in the Rejosari Health Center Work Area, Pekanbaru City. The sampling technique used is Purpose sampling. The analysis used is univariate and bivariate with the results obtained that there is a relationship between self-efficacy and adherence to physical exercise in patients with type 2 diabetes mellitus using the Pearson chi-square test. The results of this study found that among patients with diabetes mellitus, with an average age of 58.14 years, the majority were female, amounting to 59 people (72.8%), while the education level of the respondents was mostly high school graduates, amounting to 25 people (30, 9%). The majority of respondents work as IRT, which is 36 people (44.4%). As for the length of time suffering from diabetes mellitus, the respondents suffered for < 5 years, which amounted to 46 people (56.8%). Statistical test results obtained a p-value of 0.000 (